Practical Simulation of Grounded/Floating Lossy Inductors Based on Commercially Available Integrated Circuit LT1228 - Tattaya Pukkalanun; Pitchayanin Moonmuang; Sumalee Unhavanich; Worapong Tangsrirat (Advances in Science Technology and Engineering Systems Journal, 2021)
The article suggests four circuit topologies for the practical simulation of grounded and floating lossy inductors. All the suggested circuits use commercially available integrated circuit LT1228 chips as active elements, and only two passive elements, namely one resistor and one capacitor. The first two of the proposed circuits employ only a single LT1228 active element and can realize grounded lossy inductors without the need for element-matching conditions. The last two of the proposed circuits can realize synthetic floating lossy inductors with only two LT1228s. The values of simulated equivalent elements can be tuned electronically by simply adjusting the external DC bias current of the LT1228. Non-ideal transfer error effects of the LT1228 on the synthetic inductor performance are inspected. Sensitivity performance concerning transfer errors and active and passive elements is also demonstrated. PSPICE simulation results and experimental measurements of the commercially available integrated circuit, LT1228, are incorporated to corroborate all our theoretical analyses.
Keywords: Magnetic Field Sensors Techniques; High voltage insulation and dielectric phenomena; Analog and Mixed-Signal Circuit Design